The Relationship Of Self-Efficacy With Medication Adherence In Diabetes Mellitus Patients - Rochmah, Ardianti Fauziah; Abdul Muhith; Siti Nur Hasina (Journal for Quality in Public Health, 2024)
One of the successes in managing diabetes care is compliance in taking medication. Apart from that, you must have high ability and self-confidence or what is usually called self-efficacy in carrying out good diabetes management. This study aims to determine the relationship between self-efficacy and medication adherence in diabetes sufferers. This research uses a cross sectional approach. The sampling technique used in this research used purposive sampling with a sample size of 52 people with diabetes who received outpatient treatment at RSI Mabarrot MWC NU Bungah in January-February 2024. The instrument used in this research was the Diabetes Management Self Efficacy Scale questionnaire (DMSES-UK) and Morisky Medication Adherences (MMAS-8). Data analysis used the Spearman rank correlation statistical test. The results showed that of the 52 people, 44 people had high self-efficacy, with 38 people (73.1%) having high medication adherence, and 2 (3.8%) people having moderate medication adherence. The results of data analysis show a significance value of 0.000 <0.05 with a correlation coefficient value of 0.552, meaning that there is a strong relationship between self-efficacy and adherence to taking medication in diabetes mellitus sufferers. High self-efficacy will increase adherence to taking medication in diabetes sufferers, because they have a high sense of confidence in managing diabetes care.